Reading blue jeans clothing and culture - Stage Fright Productions; Learning Seed Company (Chicago, Ill. : Learning Seed, 2009)
This program speaks about the interaction of culture and clothing and offers clues to who we are today because of it
Title from title screen
Teaching guide for this program is available at www.learningseed.com
Narrator: Kate Burns
With English subtitle
Keywords: Clothing and dress